Effect of radiation damage and illumination variability on signal‐to‐noise ratio in X‐ray free‐electron laser single‐particle imaging. Issue 6 (12th October 2020) - Gureyev, Timur E.; Kozlov, Alexander; Morgan, Andrew J.; Martin, Andrew V.; Quiney, Harry M.
Abstract : The signal‐to‐noise ratio and spatial resolution of 3D coherent diffractive imaging are investigated, taking into account the effects of radiation damage to the sample and variability of the incident X‐ray intensity. The results are expected to be useful for the design and analysis of X‐ray free‐electron laser‐based imaging experiments. Abstract : The deterioration of both the signal‐to‐noise ratio and the spatial resolution in the electron‐density distribution reconstructed from diffraction intensities collected at different orientations of a sample is analysed theoretically with respect to the radiation damage to the sample and the variations in the X‐ray intensities illuminating different copies of the sample. The simple analytical expressions and numerical estimates obtained for models of radiation damage and incident X‐ray pulses may be helpful in planning X‐ray free‐electron laser (XFEL) imaging experiments and in analysis of experimental data. This approach to the analysis of partially coherent X‐ray imaging configurations can potentially be used for analysis of other forms of imaging where the temporal behaviour of the sample and the incident intensity during exposure may affect the inverse problem of sample reconstruction.